The Semiological Methodology: Heteronormative Limits and Hidden Researcher - Castelán, Claudia; Matzner, Natalia (Instituto de Estudios Avanzados - Universidad de Santiago de Chile, 2019)
This paper elaborates an analysis concerning semiological methodology and its application to a particular case study: the picture and footnote which acompany the description of “crossplay” found in the virtual encyclopedia Wikipedia (spanish version).  The authors reflect on the limits and posibilities that this methodology offers in its application to the image and text, questioning the ideological position of the researcher, the heteronormativity of language and its polisemyc potential. This paper traces a brief trajectory of the usage of semiology in subcultural studies and gender performativity studies in queer theory, with a reflection on situated knowledges that has an impact on the epistemological field in this type of applied method.